Recognition Of Children From Siri Marriages In The Perspective Of Islamic Family Law: Analysis Of Legal Status And Civil Rights - Saepudin Bahri (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
A siri marriage is a marriage that is valid according to Islamic law but is not officially registered with the state, thus creating legal problems for children born from such marriages. Children from siri marriages often face difficulties in obtaining legal recognition, birth certificates, and civil rights such as lineage rights, alimony, inheritance, and guardianship. This article discusses the recognition of children from siri marriages from the perspective of Islamic family law and Indonesian national law. The analysis shows that, religiously, children remain legitimate if their parents ' marriage fulfills the pillars and requirements of marriage, while state law requires official registration in order to protect the rights of children. The mechanism of marriage confirmation (marriage confirmation) validation) in the Religious Court and the decision of the Constitutional Court serve as a means to bridge this difference, so that children obtain legal recognition and full protection. This study emphasizes that the recognition of children is in line with the principle of ?if? al-nasl, which is to protect offspring so that their rights are not harmed, and is an effort to harmonize religious law and positive law.